FEM SIMULATION AND EXPERIMENTAL PROCEDURE FOR ROLL BONDING OF KIRIGAMI-TYPE COMPOSITES (Modern Problems of Metallurgy, 2025)
The study investigates the application of kirigami techniques in engineering to produce multilayer composite materials with programmable mechanical properties. The primary objective is to develop and validate a mathematical model for the roll-bonding process of an aluminum matrix reinforced with a steel expanded metal mesh. The model has been developed in the QForm UK environment using the finite element method, taking into account the relevant rheological properties of the materials and boundary conditions. Experimental roll-bonding studies were carried out on laboratory duo and quarto rolling mills at temperatures up to 500 °C and various degrees of deformation (20–50 %). The results of the numerical simulations are in agreement with the experimental data regarding changes in mesh geometry and strain distribution. It was found that even at a small degree of deformation (20 %), it is possible to form an effective bond with a “zip-bonding” effect; but that such a bond is unstable. It is therefore advisable to apply a degree of deformation greater than 30% in the roll-bonding process. The results of the study can be used for the further development of manufacturing technologies for functional kirigami structures based on metal composites.
Keywords: roll bonding; expanded steel mesh; aluminum matrix; FEM simulation.